Association of glucocorticoid receptor gene polymorphisms with systemic lupus erythematosus in a Chinese population. (6th October 2017) - Chen, Yang‐Fan; Xu, Jian‐Hua; Zou, Yan‐Feng; Lian, Li; Wang, Fen; Chen, Shan‐Yu; Cai, Jing; Li, Mu
Abstract: Objectives: To identify the association of glucocorticoid receptor (GR) gene polymorphism with systemic lupus erythematosus (SLE). Methods: A case‐control study was carried out, in which 400 Chinese patients with SLE and 400 normal people were enrolled. DNA was extracted using a genomic DNA extraction kit, and tagged single nucleotide polymorphisms (SNPs) were identified by Haploview (4.0) Project from the Chinese HapMap Project. Eighteen tagged SNPs of the GR gene were genotyped by the Multiplex SNaPshot technique. Results: Two GR gene SNPs were associated with the pathogenesis of SLE: rs6865292 (dominant model: crude odds ratio [OR] = 1.526, 95% CI: 1.151–2.025, P = 0.003; adjusted OR = 1.525, 95% CI: 1.149–2.023, P = 0.004; P BH = 0.036) and rs9324921 (dominant model: crude OR = 1.556, 95% CI: 1.173–2.062, P = 0.002; adjusted OR = 1.553, 95% CI: 1.171–2.060, P = 0.002; P BH = 0.036). The haplotype analysis of GR gene SNPs manifested that the haplotype of 'CCGGG' (OR = 2.701, 95% CI: 1.348–5.410, P = 0.004; P BH = 0.036) was a risk factor for the development of SLE. A lower frequency of A‐allele of SNP rs4607376 ( P = 0.021; OR = 0.794, 95% CI: 0.652–0.966, P BH = 0.126), higher frequency of C‐allele of SNP rs6865292 ( P = 0.019, OR = 1.317, P BH = 0.126) and A‐allele of SNP rs9324921 ( P = 0.019, OR = 1.317, P BH = 0.126) may be risk factors for developing SLE. The rs7719514 (recessive model: crude P = 0.044; adjusted P = 0.044, P BH = 0.264), rs7701443 (recessive model: crude P = 0.044, adjusted P = 0.045; P BH = 0.264), rs4607376 (recessive model: crude P = 0.027; adjusted P = 0.026; P BH = 0.264) and haplotype 'CAGCG' ( P = 0.044; P BH = 0.198) showed marginal association with the pathogenesis of SLE. In the case group, there were no significant differences between non‐lupus nephritis and lupus nephritis. Further, we found that the SNP rs12054797 ( F = 3.228, P = 0.041, P BH = 0.342), rs2963156 ( F = 3.163, P = 0.043, P BH = 0.342) might be marginally associated with disease activity. Conclusions: The study indicates that GR genetic polymorphisms may play a major role in the pathogenesis and development of SLE.